From an African Oral Tale to an English Picture Book: Rwandan Teachers’ Experience with Online Translation of South African Institute of Distance Education’s African Storybooks (Teacher Education through Flexible Learning in Africa (TETFLE), 2021)
Research findings pertaining to language education and distance education point to the lack of online reading materials written in African languages and reflecting African contexts. Such a shortage is a challenge to literacy skills development in Africa. In Rwanda, although there are some graded readers to support the teaching of reading in Kinyarwanda, there is a shortage of enjoyable storybooks on which children can practice their reading skills. This paper contributes to addressing this challenge by investigating the partnership between the University of Rwanda-College of Education and South African Institute of Distance Education’s (Saide) African Storybook Initiative, which provides a website of digital storybooks in Kinyarwanda and other languages for early grade reading. Data were collected from 32 Rwandan teacher educators who participated in a workshop. Participants created online picture storybooks in Kinyarwanda, translated some from other languages and published them on the African Storybook website. The researchers firstly observed their activities during the workshop, then, all participants filled in the questionnaire and ten teachers were interviewed on opportunities offered and challenges encountered during the translation process. The key finding is that teachers’ experiences with translation revealed differences in story reading levels between the original Kinyarwanda folktales and English translated versions. They found special features of African agglutinating languages in determining reading levels, and foreignization of translated stories based on cultural clashes. Differences in length between the original and the translated stories were observed, as well as the specificity of English versions in reinforcing more critical thinking than the translated Kinyarwanda versions. The paper recommends teacher educators and translators to bear in mind that adaptation to African languages requires care and a high level of ability to maintain the meaning and moral lesson of the original tale and make it enjoyable for children. Translating and adapting stories from English into agglutinative African languages have implications for early grade reading interventions in African schools since children stories on African storybook website are available in more than 100 African languages.
Keywords: African storybook initiative; early years reading; Kinyarwanda folktales; agglutinating language; Saide; University of Rwanda-College of Education